A randomized clinical trial evaluating the safety and efficacy of sitagliptin added to the combination of sulfonylurea and metformin in patients with type 2 diabetes mellitus and inadequate glycemic control: 一项评估联合使用磺脲与二甲双胍治疗后血糖仍然控制不佳的2型糖尿病患者加用西格列汀治疗后的安全性与有效性的随机临床试验. (3rd February 2016) - Moses, Robert G.; Round, Elizabeth; Shentu, Yue; Golm, Gregory T.; O'neill, Edward A.; Gantz, Ira; Engel, Samuel S.; Kaufman, Keith D.; Goldstein, Barry J.
Abstract: Background: Type 2 diabetes mellitus (T2DM) treatment generally requires multiple antihyperglycemic agents. When diet, exercise, and treatment with sulfonylurea and metformin do not achieve glycemic goals, several options are available. The present study evaluated the efficacy and tolerability of sitagliptin 100 mg/day added to therapy with sulfonylurea and metformin. Methods: Patients with HbA1c ≥7.5% and ≤10.5% while on a sulfonylurea and metformin were randomized 1: 1 to sitagliptin 100 mg/day or placebo for 24 weeks. At Week 24, patients in the placebo group switched to pioglitazone 30 mg/day and both groups continued treatment for another 30 weeks. Results: Of 427 patients randomized, 339 (79.4%) completed the study. At Week 24, significantly greater ( P < 0.001) mean reductions from baseline were seen in the sitagliptin versus placebo group for HbA1c (−0.84% vs −0.16%, respectively), 2‐h post‐meal glucose (−2.0 vs −0.2 mmol/L, respectively) and fasting plasma glucose (−0.7 vs 0.3 mmol/L, respectively). At Week 54, improvements in glycemic control continued. At Week 24, the incidence of adverse events (AEs) was numerically greater with sitagliptin than placebo, primarily because of a higher incidence of hypoglycemia. At Week 54, the incidence of AEs was similar in both groups, primarily because of a higher incidence of hypoglycemia and edema in the placebo/pioglitazone group after Week 24. The only meaningful change in body weight was an increase in the placebo/pioglitazone group at Week 54. Conclusions: In this study, sitagliptin 100 mg/day was generally well tolerated and provided improvement in glycemic control when added to the combination of sulfonylurea and metformin in patients with T2DM. Abstract : Highlights In a randomized, placebo‐controlled double‐blind clinical trial occurring primarily in the Asian‐Pacific region, sitagliptin 100 mg/day compared with placebo was generally well tolerated and provided improvement in glycemic control when added to the combination of sulfonylurea and metformin in patients with type 2 diabetes.